(R)evolution-on-a-chip. Issue 1 (January 2022) - Bouzetos, Evgenios; Ganar, Ketan Ashok; Mastrobattista, Enrico; Deshpande, Siddharth; van der Oost, John
Abstract : Billions of years of Darwinian evolution has led to the emergence of highly sophisticated and diverse life forms on Earth. Inspired by natural evolution, similar principles have been adopted in laboratory evolution for the fast optimization of genes and proteins for specific applications. In this review, we highlight state-of-the-art laboratory evolution strategies for protein engineering, with a special emphasis on in vitro strategies. We further describe how recent progress in microfluidic technology has allowed the generation and manipulation of artificial compartments for high-throughput laboratory evolution experiments. Expectations for the future are high: we foresee a revolution on-a-chip. Highlights: High-throughput droplet generation using on-chip microfluidics allows for screening genetic expression libraries in monodisperse compartments in which a genotype to phenotype linkage is maintained. Synthetic compartments are compatible with in vitro expression of genes, making them ideal containers for laboratory evolution. Fluorescence-independent screening methods increase the scope of microfluidics-assisted in vitro compartmentalization (μΙVC). μΙVC is progressing rapidly from pilot stage to industrial applications.